О взаимодействии перфекта и вида в литовском языке - Geniušienė, Ema (Baltistica, 1989)
ON THE INTERACTION OF PERFECT AND ASPECT IN LITHUANIAN This paper is concerned with the range of meanings of perfect forms determined by the aspectual (perfective and imperfective) value of the verb and with the relation of the meanings of perfect forms to the meanings of aspects in Lithuanian. Perfect forms „būti ‘be’ + past participle active” can render the perfect meaning proper of a previous situation with continuing relevance and the resultative meaning of a state of the deep subject resulting from a previous situation. Aspect is the major factor determining the perfect or resultative use of perfect forms. The resultative meaning can be rendered by the perfect form of perfective verbs exclusively, the perfect meaning being rendered by the said form of verbs of either aspect. In the perfect use, a verb retains its aspectual value. In the resultative use a verb changes its perfective value to imperfective and therefore it can function as a substitute for a missing imperfective verb in an aspect opposition. The invariant perfect meaning has a number of variants largely determined by the aspectual value of the base verb.